Anomalies and Methodology of Science - Sýkora, Peter (Teorie vědy / Theory of Science, 2017)
Book review: Vladimír Havlík. Anomálie, ad hoc hypotézy a temné stránky kosmologie. Plzeň: Západočeská univerzita v Plzni, 2015, 165 pages.